Seismic performance of RC precast industrial buildings—learning with the past earthquakes - Batalha, Nádia (2019)
Precast reinforced concrete (RC) industrial buildings have exposed their vulnerability on recent earthquakes, highlighting structural and non-structural damages most related to deficient transferring of horizontal forces namely in connections between elements. Several studies have been carried out on the evaluation of seismic vulnerability of RC structures, motivated mainly by the need of protecting the existent building stock and human lives. However, the same concern is also relative to the industrial building stock, where precast reinforced concrete building is one of the main structural systems. The collapse of such type of structures can result in important losses of human lives and lead to also large economic impact on society. Severe damages can limit its reparability after earthquake events, which result in its demolition and reconstruction. It was this context of damages that emphasized the need for risk assessment to estimate potential damage for future earthquakes. Thus, the main objective of the present paper is to review and identify the main sources that can increase the vulnerability of this typology of buildings to allow the proper seismic assessment of existing precast industrial buildings and solve the inefficient structural and non-structural problems with innovative techniques for its retrofitting.